Egypt Economic Monitor, November 2020 : From Crisis to Economic Transformation - Unlocking Egypt’s Productivity and Job-Creation Potential - World Bank (World Bank, Washington, DC, 2020)
The COVID-19 (coronavirus) pandemic is causing the most severe global health and economic crisis in at least seven decades. In Egypt, the disruptions caused by the pandemic started in March 2020, and has since interrupted a period of macroeconomic stability, characterized by relatively high growth, improved fiscal accounts, and a comfortable level of foreign reserves. Yet, the pandemic also hit as longstanding challenges continued to persist, notably the government’s elevated debt-to-GDP ratio (despite its significant reduction in recent years), sluggish revenue-mobilization and the below-potential performance of non-oil merchandise exports and non-oil FDI. The fiscal, monetary and energy sector reforms implemented in recent years, along with the emergency measures undertaken by authorities in response to the COVID-19 crisis are so far helping Egypt weather the shock. Indeed, average real growth has remained positive during FY2019/20 and foreign reserves continue to be rather ample. Nevertheless, the COVID-19 pandemic has inevitably caused job and income losses, posing additional strains on Egyptian households’ livelihoods, and is thus exacerbating the long-standing challenge of job-creation in Egypt, notably in the formal private sector. The in-focus chapter of this report is therefore dedicated to the topic of jobs and economic transformation. The analysis of this chapter shows that the economic transformation process has been slow-moving in Egypt, with employment shares increasing either in low value-added sectors, or in sectors that have experienced a decline in productivity (value-added per worker). Hence, the Egyptian economy has not been able to generate high-earning jobs, at scale. Going forward, for businesses to expand and create sufficient and high-quality employment opportunities, a three-pronged approach will be necessary: (i) Sustaining macroeconomic stability and overall policy predictability whilst incentivizing domestic savings to finance investments. (ii) Getting the enabling environment right to create attractive opportunities for domestic and foreign investments. (iii) Upgrading human capital and firm capabilities to fast-track the economic transformation process in Egypt and to strengthen the country’s resilience against such severe shocks.